Physiological Assessment of Ventricular Myocardial Voltage Using Omnipolar Electrograms. Issue 8 (16th August 2017) - Magtibay, Karl; Massé, Stéphane; Asta, John; Kusha, Marjan; Lai, Patrick F. H.; Azam, Mohammed Ali; Porta‐Sanchez, Andreu; Haldar, Shouvik; Malebranche, Daniel; Labos, Christopher; Deno, D. Curtis; Nanthakumar, Kumaraswamy
Abstract : Background: Characterization of myocardial health by bipolar electrograms are critical for ventricular tachycardia therapy. Dependence of bipolar electrograms on electrode orientation may reduce reliability of voltage assessment along the plane of arrhythmic myocardial substrate. Hence, we sought to evaluate voltage assessment from orientation‐independent omnipolar electrograms. Methods and Results: We mapped the ventricular epicardium of 5 isolated hearts from each species—healthy rabbits, healthy pigs, and diseased humans—under paced conditions. We derived bipolar electrograms and voltage peak‐to‐peak (Vpps) along 2 bipolar electrode orientations (horizontal and vertical). We derived omnipolar electrograms and Vpps using omnipolar electrogram methodology. Voltage maps were created for both bipoles and omnipole. Electrode orientation affects the bipolar voltage map with an average absolute difference between horizontal and vertical of 0.25±0.18 mV in humans. Vpps provide larger absolute values than horizontal and vertical bipolar Vpps by 1.6 and 1.4 mV, respectively, in humans. Bipolar electrograms with the largest Vpps from either along horizontal or vertical orientation are highly correlated with omnipolar electrograms and with Vpps values (0.97±0.08 and 0.94±0.08, respectively). Vpps values are more consistent than bipoles, in both beat‐by‐beat (CoV, 0.28±0.19 versus 0.08±0.13 in human hearts) and rhythm changes (0.55±0.21 versus 0.40±0.20 in porcine hearts). Conclusions: Omnipoles provide physiologically relevant and consistent voltages that are along the maximal bipolar direction on the plane of the myocardium.